Negotiating censorship in the postwar spanish novel divorce and civil marriage in Elena Quiroga’s algo pasa en la calle (1954) - Leggott, Sarah (Revista de Escritoras Ibéricas, 2014)
n recent years, the postwar Spanish novel has received relatively little critical attention, with much scholarship focusing instead on more contemporary works that deal with the Civil War and its legacy. My argument in this article is premised on the notion that works produced in 1950s and 1960s Spain merit renewed scholarly attention and a fresh critical approach. I focus my discussion on the works of novelist Elena Quiroga, whose works have been the focus of little scholarly attention and are generally not well-known by the reading public. My discussion considers the reasons for this neglect of Quiroga and her works, examining her narrative style and her treatment of highly contentious issues in her works, despite the strict censorship regime in place in postwar Spain. My analysis centres on Algo pasa en la calle, Quiroga’s most experimental novel of the 1950s in terms of technique, and also the most daring in terms of social criticism. I examine the author’s representation of the contentious issue of divorce and civil marriage, and her subversion of the gendered identities prescribed in Franco’s Spain.